2015
DOI: 10.4172/2471-2701.1000106
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age upon Leadership Attributes from Recruitment Instrument: a Selective Developmental Trajectory

Abstract: This exploratory report presents the contents of a large data-base consisting of psychometric measurement of personality-related attributes of individuals who underwent the recruitment process by completing the JobMatchTalent instrument that was developed from principles of occupational psychology. On the basis of individuals', who applied for corporate or governmental leadership positions, responses, the correlations between applicants' age and personal attributes was obtained. Correlational and regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…In a replicative study based upon executives' estimations of work performance at recruitment, using the JobMatchTalent (JMT) database [2,3] administrators' estimations of employees' performance and 'work-ability' , as assessed by the JMT recruitment instrument [4]. The study involved 258 recruited employees, who had responded to the JMT instrument, consisting of three main scales wherein each scale was comprised of three sub-scales, at recruitment and 94 executiveadministrations.…”
Section: Introductionmentioning
confidence: 99%
“…In a replicative study based upon executives' estimations of work performance at recruitment, using the JobMatchTalent (JMT) database [2,3] administrators' estimations of employees' performance and 'work-ability' , as assessed by the JMT recruitment instrument [4]. The study involved 258 recruited employees, who had responded to the JMT instrument, consisting of three main scales wherein each scale was comprised of three sub-scales, at recruitment and 94 executiveadministrations.…”
Section: Introductionmentioning
confidence: 99%
“…The JMT test is based on ten main scales, each presenting three subscales, and has been shown to possess a high level of congruence with health-and personality-related instruments [26]. For a detailed description of the scales, see [17].…”
Section: Instrumentmentioning
confidence: 99%
“…To this end, the Job Match Talent test estimates individuals' attributes that are associated with occupational leadership roles in relation to type of enterprise, level of leadership and the age-at-recruitment of applicants. In a large exploratory report, consisting of a data-base derived from over 6700 recruitment participants seeking leadership positions, the psychometric measurement of personality-related attributes of individuals who had applied for executive positions displayed marked and consistent relationships between the participants' age-group and their self-reported personal profiles [17]. It was shown that at the higher age levels the candidates for executive leadership positions expressed a lesser interest and focus upon the specific aspects of the tasks associated with 'job-performance' and lesser orientation towards their own personal ambitions and goals; they expressed rather greater concern for the development of their staff and teams and shaping relationships within the teams within which they functioned.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation